Характеристика основних рис особистості працівника міліції 1920-х років: спроба історико-психологічної реконструкції - Греченко, В. А.; Grechenko, V. A.; Посохова, Я. С.; Posokhova, Y. S.; ResearcherID: I-7336-2016; Пономаренко (Посохова) Яна Сергіївна (Право і безпека. – 2017. – № 4 (67). – С.142-148, 2017)
Проаналізовано основні аспекти психології працівника міліції в Українській СРР у 1920-х роках. Основну увагу приділено чинникам, які впливали на формування особистості працівника міліції, зокрема подіям збройної боротьби Української революції 1917–1921 рр., соціальному походженню працівників, їх загальноосвітньому та політичному рівню, впливу національної психології, соціально-економічним умовам нової економічної політики.

It has been noted that after the establishment of Soviet power in Ukraine, there was the formation of law enforcement agencies. Militia of the Ukrainian SSR was organized from purely class positions. The soldiers and commanders of the Red Army, who joined the ranks of militia, brought with them the psychology inherent in the era of war and revolution. The guardians of the order were ordinary people, the so-called People’s Militia. Its activity was designed to form a new image of a guardian of law and order in the minds of Ukrainian people, which over time repeatedly was transformed and acquired new personal traits inherent in this social group. The distribution of indicators for socio-economic parameters such as nationality, social origin, educational level indicates that they did not play a significant role in the development of the personality of a young specialist – a militiaman, and were not taken into account during professional selection in the ranks of law enforcement system. That is, it can be said that the psychological selection, which would determine the ability or disability of service, was also not carried out to the extent that was necessary for the successful and effective performance of professional duties. The low educational level and elemental ignorance in everyday matters led to the fact that the level of work performed by militiamen was low and did not solve the main tasks that were assigned to them. The professional activity of a militiaman was characterized by ignoring procedural requirements and restrictions, abuse of position, which led to the development of legal nihilism. Militia squads were predominantly formed of ordinary peasants and workers, whose level of intellectual, educational, cultural, emotional and mental development was insufficient to carry out the professional duties of the law enforcement system, and, as a result, personnel clearance took place among militiamen in the course of time.

Проанализированы основные аспекты психологии работника милиции в Украинской ССР в 1920-е годы. Основное внимание уделено факторам, которые влияли на формирование личности сотрудника милиции, в частности событиям вооружённой борьбы Украинской революции 1917–1921 гг., социальному происхождению работников, их общеобразовательному и политическому уровню, влиянию национальной психологии, социально-экономическим условиям новой экономической политики.
Characteristics of basic features of a personality of militia officer of 1920s: attempt of historical and psychological reconstruction
Характеристика основных черт личности работника милиции 1920-х годов: попытка историко- психологической реконструкции
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Психологія. Рsychology. Психология; Юридична психологія. Legal psychology. Юридическая психология; Історія. History. История; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Internal Affairs Agencies; органы внутренних дел; міліція; історична психологія; особистість; історична реконструкція; militia; historical psychology; personality; historical reconstruction; милиция; историческая психология; личность; историческая реконструкция